Colonization of gerbils with Helicobacter pylori O‐chain‐deficient mutant SS1 HP0826:Kan results in gastritis and is associated with de novo synthesis of extended homopolymers. Issue 2 (25th February 2013) - Chandan, Vandana; Jeremy, Anthony H.T.; Dixon, Michael F.; Altman, Eleonora; Crabtree, Jean E.
Abstract The O‐chain polysaccharide of Helicobacter pylori is important for colonization and generation of chronic gastritis in mice. There are marked host differences in the development of H. pylori‐induced gastric pathology in mice and gerbils. To investigate the role of the O‐chain polysaccharide of H. pylori in colonization and gastritis in Mongolian gerbils, inoculation by oral gavage with H. pylori strain SS1 and its corresponding O‐chain polysaccharide‐deficient mutant SS1 HP0826::Kan was undertaken. Infection with both strains resulted in corpus atrophy, loss of parietal cells, and extensive mucous metaplasia at both 18 and 30 weeks postinfection. Contrary to previous results in splenocyte recipient severe combined immunodeficiency (SCID) mice, no difference was found in the grade of chronic gastritis, polymorphonuclear cell infiltration, atrophy, and mucous metaplasia in gerbils infected with the wild‐type SS1 strain or SS1 HP0826::Kan strain. Examination of the effects of gerbil passage on LPS profiles of output SS1 HP0826::Kan isolates by SDS‐PAGE, sugar, and methylation analyses revealed significant differences in LPS profiles of SS1 HP0826::Kan cells recovered from infected gerbils as compared to input bacteria. Specifically, the presence of a novel homopolymer of d‐galactan, as well as an extended polymer of d‐riban, was detected. These data provide evidence for the role of H. pylori LPS in bacterial adaption to promote colonization and pathology.